Seriously funny: The political work of humor on social media. (October 2018) - Davis, Jenny L; Love, Tony P; Killen, Gemma
Research shows a clear intersection between humor and political communication online as "big data" analyses demonstrate humorous content achieving disproportionate attention across social media platforms. What remains unclear is the degree to which politics are fodder for "silly" content production vis-à-vis humor as a serious political tool. To answer this question, we scraped Twitter data from two cases in which humor and politics converged during the 2016 US presidential election: Hillary Clinton referring to Trump supporters as a "basket of deplorables" and Donald Trump calling Hillary Clinton a "nasty woman" during a televised debate. Taking a "small data" approach, we find funny content enacting meaningful political work including expressions of opposition, political identification, and displays of civic support. Furthermore, comparing humor style between partisan cases shows the partial-but incomplete-breakdown of humor's notoriously firm boundaries. Partisan patterns reveal that the meeting of humor and social media leave neither unchanged.